(3TQM bhGYO GdCMcGe aj eYQaI GdMdGd hGdMQGes - (3Ydj Hf YHO GdYGdi GdeMbb GdcQcis; (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3GdeJGLQ gi LeY eJLQ hSdei HeYfi GdJLGQI s
(3BNQgG (B:s
(3hCeG fai OYhGg Yf faS abW hde jJYQV ddfai CUd Gdedc s
(3GdfSNI HgG MhGTs
(3hQO PcQ GdYfhGf GdCUdi ai EjVGM Gdecfhf ai (B242/2s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B303s
Keywords: (3abg GdePGgH GdCNQis